Исследовательская деятельность как основа современного образования - Shabalina E. P., Piatkina D. A. (Педагогический опыт: теория, методика, практика, 2016)
The problem of research. The authors of the research activities are considered as a special kind of intellectual and creative activity of students in high school.
Keywords: исследовательская деятельность; развитие; research; учебно-исследовательская работа; становление специалиста; компетенции исследовательской работы; development; teaching and research; the development of specialist research competence